Private Settlement of Crimes: Bartolus’ Doctrine (Italian Review of Legal History, 2020)
The author of a crime could reach an agreement with his victim if, and only if, the law hit him with a capital punishment: such was the law established by a constitution by Diocletian (Cod. Iust. 2. 4. 18, lex Transigere), that the mediaeval doctores discussed at length since the age of the early bolognese Glossators. Bartolus’ Commentary faces every aspect of this provision, that deserved careful scrutiny in order to clarify its grounds (rationes), its limits, and the relationship with several other texts of the Corpus iuris seemingly contradicting (as oppositiones) the rule of the law. His commentary to the lex Transigere discusses: (a) the ratio and the limits of the provision permitting (for the crimina capitalia) or preventing (for the further crimes) the agreement; (b) the possible extension of those rules to the delicta private; (c) the ground of the two exceptions provided by the same law, concerning the adultery (agreement vetoed) and the crimen falsi (agreement permitted); d) the coordination of the lex with the urban statuta. The work of Bartolus on this topic includes a relevant Quaestio and a Consilium, both in line with his Commentaries. The relationship of the theoretical work with the specific features of tdure of its time - including the reforms introduced by the local statutes and the recent new inquisitorial powers of the judges - are also carefully taken into account by the great jurist of Sassoferrato.
Keywords: delicta; crimina and pax privata; crimes’ private settlement; Bartolus.